Cross-sectional patterns of mortgage debt during the housing boom: Evidence and implications - Christopher L. Foote; Lara Loewenstein; Paul S. Willen (Federal Reserve Bank of Boston, 2016)
The reallocation of mortgage debt to low-income or marginally qualified borrowers plays a central role in many explanations of the early 2000s housing boom. We show that such a reallocation never occurred, as the distribution of mortgage debt with respect to income changed little even as the aggregate stock of debt grew rapidly. Moreover, because mortgage debt varies positively with income in the cross section, equal percentage increases in debt among high- and low-income borrowers meant that wealthy borrowers accounted for most new debt in dollar terms. Previous research stressing the importance of low-income borrowing was based on the inflow of new mortgage originations alone, so it could not detect offsetting outflows in mortgage terminations that left the allocation of debt stable over time. And while defaults on subprime mortgages played an important part in the financial crisis, the data show that subprime lending did not cause a reallocation of debt toward the poor. Rather, subprime lending prevented a reallocation of debt toward the wealthy.
Keywords: D12; D14; E03; G21; R21; 330; Hypothek; Immobilienpreis; Konjunktur; USA